SHAYXZODA HAQIDA (Journal of Universal Science Research, 2023)
This article notes the childhood of Maqsud Shaykhzoda, an Azerbaijani artist, who has a special place in Uzbek literature, not only as a poet, but also as a strong playwright, literary scholar and educator. It is about the artist’s love of literature, his first poem and his student years. His pedagogical activity, modern works, the artist's attitude to the time are reflected.